Human Metapneumovirus (HMPV): Epidemiology, Pathophysiology, Clinical Management, and Future Prospects in Treatment and Prevention - Ahmed, Rashed (RADINKA JAYA UTAMA PUBLISHER, 2025)
Human metapneumovirus (HMPV) is a significant respiratory pathogen that primarily impacts children, the elderly, and immunocompromised individuals. This article provides a comprehensive overview of HMPV, highlighting its epidemiology, pathophysiology, clinical presentation, and current treatment approaches. Key research objectives are delineated, emphasizing the importance of understanding molecular mechanisms, epidemiological trends, and therapeutic strategies. This review also explores the historical discovery of HMPV, its clinical manifestations ranging from mild upper respiratory tract infections to severe lower respiratory conditions, and its disease progression. A detailed treatment algorithm outlines both pharmacologic options, such as experimental antivirals and monoclonal antibodies, and non-pharmacologic measures, including oxygen therapy and preventive strategies. Comparisons with SARS-CoV-2 underscore similarities in clinical spectrum and transmission while emphasizing critical differences in epidemiology and available treatments. Current research findings are analyzed to provide insights into the global burden of HMPV and its interaction with other respiratory viruses. Finally, future prospects in vaccine development, diagnostic advancements, and public health measures are discussed to highlight the need for continued research and global preparedness.